The emergence of representative system in the local self-government: the Swedish case - Pivoras, Saulius (Politologija, 2000)
This article analyses factors, which determined social and territorial representativity of high level in the Swedish local self-government. They are identified by reconstructing circumstances of transition from direct to representative management of local affairs. Elected representative institutions in local self-government—municipal and county councils—appeared after reform of 1862. But even before then one can detect elements of the representative system. As the first representative institution in local self-government one could hold parish committee (sockennämnd). They attempted to represent various social classes and localities in the parishes. Sometimes village elders constituted the parish committee. But even before the introduction of parish committees, representation was well known in the Swedish local self-government. Dealing with certain affairs in courts or governmental institutions as well as in the encounterment with the private physical or juridical persons, it was usual to authorize somebody to represent the interested party. Villages authorized certain persons to represent their interests in the parish meetings.In this article, it is shown that the need in the parish committees became ripe from below in some parishes (at least in Northern Sweden) a few decades before the establishment of them. There existed elected with differing stipulations special parish representatives (sockenfullmäktige).It is also shown that advantages and deficiencies of municipal councils were rather widely discussed in the press and society before the introducement of obligatory councils in 1919. Discussions concentrated on the issue of how to assure representation of various social classes and, particularly, remote localities in the municipal councils. Parties, represented in the parliament, had to overcome mistrust in the countryside and to demonstrate their care for good social as well as for territorial representativity.Representative system in the Swedish local self-government developed gradually. It was a long process, the important part of which was internalization of inevitability and adequacy of the representative forms in the consciousness of ordinary citizens. General precondition of this process was not only developed political but even common culture of the Swedish people.
Keywords: -